2019
DOI: 10.1021/acs.joc.8b03132
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Chemical Characterization of Factors Affecting the Neutral and Radical-Cation Newman–Kwart Reactions

Abstract: Details of the electronic and geometric structures of stationary points along the reaction coordinate of the Newman Kwart rearrangement, which transforms an O-arylthiocarbamate to an S-arylcarbamothioate, are examined using quantum chemical methods for a large number of compounds considering both the thermal reactions of uncharged substrates as well as the corresponding reactions of radical cation substrates generated under photoredox conditions. The uncharged mechanism, which has intrinsically high 298 K free… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 37 publications
1
13
0
3
Order By: Relevance
“…More recently, a radical cation version of the Newman–Kwart rearrangement has been discovered that proceeds under mild conditions and that has quite a different response to substituents than in the thermal rearrangement. Cramer has reported recent studies that provide further computational characterisation of the thermal Newman–Kwart rearrangement as well as its radical cation counterpart; the radical cation variant is also viewed as being a concerted substitution reaction …”
Section: Newman–kwart and Related Rearrangementsmentioning
confidence: 99%
See 3 more Smart Citations
“…More recently, a radical cation version of the Newman–Kwart rearrangement has been discovered that proceeds under mild conditions and that has quite a different response to substituents than in the thermal rearrangement. Cramer has reported recent studies that provide further computational characterisation of the thermal Newman–Kwart rearrangement as well as its radical cation counterpart; the radical cation variant is also viewed as being a concerted substitution reaction …”
Section: Newman–kwart and Related Rearrangementsmentioning
confidence: 99%
“…On ar elated theme,S anford et al reported am ild deoxyfluorination of phenols 97 via aryl fluorosulfonate intermediates 98. [57] This transformation was found to be compatible with ortho-, meta-, or para-electron-withdrawing groups,a nd could also be applied to electron-neutral and moderately electron-rich substrates to provide fluorinated products [100][101][102][103][104][105][106][107][108][109][110][111].…”
Section: Fluorodeoxygenation Of Phenols and Derivativesmentioning
confidence: 99%
See 2 more Smart Citations
“…Ausd en Ergebnissen wurde geschlossen, dass auch die radikal-kationische Version eine konzertierte Substitutionsreaktion darstellt. [101][102][103]…”
Section: Newman-kwart-reaktionen Und Verwandte Umlagerungenunclassified